Improving micro-climatic conditions within byre through manipulation of central ridge ventilator and eaves (Indian Journal of Animal Production and Management, 2024)
India possesses maximum number of cows and  buffaloes in the world and her countrymen rear them  mainly for harvesting their milk. Likewise India also  possesses other livestock, like sheep, goat, equines,  pigs, camel, rabbit, poultry as well as wild animals  in large numbers. Rearing of a particular species  requires rearing of different classes of animals at  the farm, for cattle: in-milk cows, suckling calves,  heifers, pregnant heifers, down calvers, dry non pregnant cows, dry pregnant cows, bull calves, bulls,  bullocks, old stock and so on, preferably in their  respective houses. However, all these categories  of cattle may not be available at a small sized farm.